2012
DOI: 10.1111/j.1442-9071.2012.02840.x
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous access to cataract surgery: an assessment of the barriers and solutions within the Australian health system

Abstract: Background:  To identify barriers in the health systems that limit access to cataract surgery for Indigenous Australians and present strategies to overcome these barriers.Design:  Interview and focus group‐based qualitative study.Participants:  Five hundred thirty participants were consulted in semi‐structured interviews, focus group discussions and stakeholder workshops.Methods:  Semi‐structured interviews with a cross‐section of health‐care professionals, eye care practitioners, primary health‐care workers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Similar results have been found in the United States, 33 where 63% of subjects had undetected eye disease; insurance coverage (cost) was also a factor associated with poor access to care. Findings from other studies [34][35][36] agree that education, lack of knowledge that a problem exists, cost, fear, fatalism, ageism, and the ability to cope were also important barriers.…”
mentioning
confidence: 73%
“…Similar results have been found in the United States, 33 where 63% of subjects had undetected eye disease; insurance coverage (cost) was also a factor associated with poor access to care. Findings from other studies [34][35][36] agree that education, lack of knowledge that a problem exists, cost, fear, fatalism, ageism, and the ability to cope were also important barriers.…”
mentioning
confidence: 73%
“…Although the data analyzed for this report did not allow us to quantify access to or acceptance of medical care, others have found many barriers to Aboriginal people receiving optimal medical and surgical care for chronic diseases, related to healthcare systems, remoteness, and cultural factors. 22,23 In the case of RHD, there is the added complication that cardiac surgery is not available in the NT, so surgical intervention involves travel to cities many thousands of kilometers away. If outcomes for RHD are to be improved in similar settings, healthcare services must improve the capacity of the health workforce, the availability of specialist care, the systems for delivering care to patients with complex, chronic diseases, and the mechanisms to address cultural impediments to uptake of Western medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Providers of non‐clinical support are both health system‐based (clinicians, coordinators, administrators), and community‐based (Elders, family, school staff). We found that patient liaison and case management is central to the coordination of eye care services, particularly given patient distrust and fear of cataract surgery . A key finding was the prominent role of eye health coordinators in providing these types of non‐clinical support.…”
Section: Discussionmentioning
confidence: 94%
“…27,30 Secondary and tertiary eye care coordination included organising and facilitating surgery attendance, booking travel and accommodation for ophthalmic care, and ensuring appropriate follow-up care. 38,41 Key providers of eye care coordination and associated support included eye health coordinators, 11,12,[24][25][26]30,34,35,40,41 Aboriginal Health Workers (AHWs), 23,25,27,34 primary health care staff, 34,38,41 and community liaison staff. 12,23 One study reported that support provided by regional eye health coordinators was intended to cover multiple communities, but in practice was delivered only to the communities where the coordinators resided.…”
Section: Coordination Of Carementioning
confidence: 99%
See 1 more Smart Citation